Defining a new Internet communication strategy at the University of Pardubice - Holá, Jana; Hloušková, Jitka (Slovenská technická univerzita v Bratislave, 2007)
A project on new Internet presentation and communication is being carried out at the University of Pardubice. The need of a new solution comes out from up-to-date requirements for communication within the increase of the University’s competitive advantage in the national as well as international environment. The Internet is becoming a more and more important source of information, for some target groups of mutual communication it is often the only one. For this reason it is necessary to optimise the currently used technology and the contents of website presentation according to new trends. The starting point for the new solutions is the formation of a University communication Internet strategy, which will comprehend the main communication objectives. This strategy should contribute to better cooperation between the University and its partners. A communication Internet strategy can help the University achieve the main goals of its long-time programme. A Communication Internet Strategy (CIS) – the usage of the Internet in the University communication process – outlines how Internet communication can help improve mutual communication between the University and its partners. This article brings an overview of the main points of the CIS definition process and its meaning for the selection and implementation of a new solution.
Keywords: Internet communication strategy (CIS); University of Pardubice; University communication processes; implementation processes